Tau protein and brain derived neurotropic factor profile in patient undergoing sevoflurane anaesthesia - Che Omar, Sanihah (2015)

(untitled)
Objective: Sevoflurane is commonly and widely used inhalational agent in general anaesthesia. The sevoflurane will be used in general anesthesia to ensure patients are not aware during the operation. Generally, anaesthesia using sevoflurance is safe but some study showed that the usage of sevoflurane can cause cognitive impairment post operatively in susceptible patient. The use of sevoflurane may cause deterioration in neurocognitive function resulting from tau hyperphosphorylation and perhaps reduced level of brain derived neurotropic factor. The purpose of this study is to investigate the effects of sevoflurane anaesthesia on the level of tau protein and brain derived neurotropic factor. Methodology: This was a cross-sectional observational study from June 2013 until October 2014 done in operation theatre Hospital Universiti Sains Malaysia (USM). 39 patients scheduled to undergo elective surgery in orthopaedic cases requiring general anaesthesia were included. Blood was obtained for baseline tau protein and BDNF before induction of anaesthesia using sevoflurane. Maintenance of anaesthesia using sevoflurane with the target minimum alveolar concentration (MAC) 1.5 -2.0 in oxygen: air, 70:30 mixture and to achieved BIS reading of 40 – 60. Throughout the surgery body temperature are maintained within normal range (T° 36- 37.5 ). Duration of anaesthesia was planned for at least 60 and up to 180 min. Once operation is finished, patient will then be extubated and observed in recovery room & will be discharged to the respective wards once they met the ALDRETE & PADSS score & reviewed by anaesthetist. Blood investigation for Tau Protein and BDNF will be repeated 24-48 hours postoperatively. ELISA assay for the plasma Tau protein and BDNF were performed to obtain the blood level for these biomarkers. Results: The mean level of pre Tau Protein was 18.63 ± SD 18.84 and the mean level post Tau Protein was 10.52 ± SD 18.52. The mean level of pre BDNF was 1.63 ± SD 1.71 and the mean level of post BDNF was 1.40 ± SD 2.06. There were no significant changes in the level of Tau Protein or Brain Derived Neurotropic Factor before or after undergoing anaesthesia using sevoflurane. Postoperatively, there were no significant differences in the level of Tau Protein or Brain Derived Neurotropic Factor after first time exposure to sevoflurane anaesthesia. Conclusions: There were no significant differences on the level of both Tau Protein and Brain Derived Neurotropic Factor after first time exposure to sevoflurane anaesthesia.